Extremely halophilic Archaea from Tuz Lake, Turkey, and the adjacent Kaldirim and Kayacik salterns - OGAN, AYŞE; ÇALLI, BARIŞ; MERTOĞLU, BÜLENT; BİRBİR, MERAL (SPRINGER, 2007)
Tuz Lake is a hypersaline lake located in Central Anatolia, Turkey. The lake and its salterns, Kaldirim and Kayacik, are the major sources of solar salt for industrial applications in Turkey, especially in the food and leather industries. Use of the crude solar salt often results in microbial deterioration of the products. We therefore initiated a thorough characterization of the microbial communities in Tuz Lake and its adjacent salterns, and we present here the results of investigations on diversity of extremely halophilic Archaea. Twenty-seven colonies of aerobic red or pink Archaea (family Halobacteriaceae) were selected according to colony shape, size, consistency and pigmentation, and characterized according to their phenotypic characteristics, polar lipid contents, and antibiotic sensitivities. Furthermore, 16S rRNA genes of the isolates were screened by DGGE analysis and partially sequenced. Phylogenetic analysis showed that most isolates belonged to the genera Haloarcula, Halorubrum and Halobacterium. Haloarcula was found to be dominant both in Tuz Lake and in the saltern samples. Halorubrum species were isolated from Tuz Lake and from the Kaldirim saltern, and Halobacterium species were recovered from Tuz Lake and from the Kayacik saltern. All strains showed various activities of hydrolytic enzymes (proteases, amylases, cellulases, and others), activities which are responsible for the detrimental effects of the crude salt in food and leather products.
Keywords: Tuz Lake; Kaldirim saltern; Kayacik saltern; Halophilic Archaea; MOLECULAR CHARACTERIZATION; BACTERIA; IDENTIFICATION; ENDOGLUCANASE; CULTIVATION; DIVERSITY; COMMUNITY; ALIGNMENT; QUALITY; POND